Imágenes de centauros en los vasos áticos de figuras negras y de figuras rojas : siglos VIII A.C.-IV A.C. - Herranz, María, (Archaeopress Publishing Ltd, 2017)
The centaur, a hybrid being with the body of horse and a human head and torso, first appeared in the mountains of Thessaly. This book is composed of a catalogue divided into nine chapters. Each chapter comprises catalogue entries for a number of black-figure and red-figure Attic vases.